Irreversible electroporation versus radiofrequency ablation for hepatocellular carcinoma: a single centre propensity-matched comparison. (3rd August 2021) - Freeman, Elliot; Cheung, Wa; Ferdousi, Sapphire; Kavnoudias, Helen; Majeed, Ammar; Kemp, William; Roberts, Stuart K.
Abstract: Background and aims: Irreversible electroporation (IRE) is a relatively new non-thermal ablative method for unresectable hepatocellular carcinoma (HCC). We aimed to compare the longer-term efficacy of IRE to the standard thermal technique of radiofrequency ablation (RFA) in HCC. Methods: All patients who underwent IRE or RFA for HCC in our centre were identified and demographic and clinical data were analysed up until 1st March, 2020. Local recurrence-free survival (LRFS) was compared between groups after propensity score matching for age, gender, Child–Pugh grade, BCLC stage, lesion size and alpha-fetoprotein (AFP) level. Results: A total of 190 HCC ablations (31 IRE and 159 RFA) were identified. After propensity score matching, we compared 25 IRE procedures (76% males, median age 62.4 years, median tumour size 20 mm) to 96 RFA procedures (84.4% males, median age 64.3 years, median tumour size 18.5 mm). LRFS did not differ between groups, with a 1-, 2- and 5-year LRFS of 80.4% (95% CI 55.8–92.2), 69.1% (95% CI 43.3–84.9) and 44.9% (95% CI 18.9–68.1%), respectively for IRE and 84.8% (95% CI 75.2–90.9), 71.3% (95% CI 58.3–81.0) and 52.1% (95% CI 35.4–66.4%), respectively for RFA ( p = .63). There were no major procedure-related complications or deaths in either group. Conclusions: Whilst IRE remains a relatively novel therapy for HCC cases where standard thermal ablation is contraindicated, the LRFS in our centre is comparable to that of RFA. IRE should therefore be considered as a treatment option in such cases when available before stage-migration to non-curative therapies such as transarterial chemoembolization (TACE).